1978
DOI: 10.1073/pnas.75.1.454
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human tumors and human malignant cell lines for BK virus-specific DNA sequences

Abstract: Most humans in the United States have been infected with BK virus (BKV), a human papovavirus. Because BKV has oncogenic properties, we have investigated whether it may be a cause of human cancer. Basic principles of tumor virology imply that BKV-induced tumors should contain BKV DNA sequences. Therefore, we assayed (by molecular hybridization) DNA The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advertisement" in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 30 publications
(25 reference statements)
1
19
0
Order By: Relevance
“…Our HindIII-G fragment probe hybridizes only 5-10% with DNAs of human Ad serotypes outside of group C (2), so these data are not applicable to non-group C Ads. In other studies similar to those reported here, we were unable to detect sequences of group A (24), group B (25), or group E (26) Ads or of human BK virus (27) in human cancer DNAs. Therefore, we have found no evidence as yet that Ads or papovaviruses are involved in human cancer.…”
Section: Discussionmentioning
confidence: 31%
“…Our HindIII-G fragment probe hybridizes only 5-10% with DNAs of human Ad serotypes outside of group C (2), so these data are not applicable to non-group C Ads. In other studies similar to those reported here, we were unable to detect sequences of group A (24), group B (25), or group E (26) Ads or of human BK virus (27) in human cancer DNAs. Therefore, we have found no evidence as yet that Ads or papovaviruses are involved in human cancer.…”
Section: Discussionmentioning
confidence: 31%
“…Moreover, DNA hybridization studies in combination with restriction endonuclease digestion do not readily detect less than an average of 0.5 genome equivalents/cell. This would explain the negative results of screening with this technique to date (Israel et al, 1978;Wold et al, 1978). Tissue or tumour dissociation by mechanical or detergent means followed by PEG-mediated cell fusion with permissive cells, might induce an appropriate amplification of the number of infected cells (to at least 1 in I000) such that flow fluorimetric screening of large numbers of cells for immunofluorescence by virus antigens might yield positive results.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of BK virus DNA has been reported in DNA isolated from several human tumours (Fiori & di Mayorca, 1976). However, further studies (Wold et al, 1978) have failed to confirm these observations. DNA extracted from purified BK virus is heterogeneous in size and includes unit length infectious molecules as well as defective molecules.…”
Section: Molecular Cloning Of Infectious Dna From Human Papovavirus Bmentioning
confidence: 53%